The Importance of Mother Tongue Lessons in the Formation of Spiritual and Moral Virtues of Primary School Students - Fayzullayeva Shahzoda Akmalovna; Abdullayeva Dilshoda Otabekovna (Research Parks Publishing LLC, 2020)
Mother Tongue lessons play an important role in shaping the spiritual and moral qualities of primary school students. Educate students first and foremost through mother tongue lessons, then education. Education is the foundation of education. The mother tongue is a necessary source for this foundation. The First President of the Republic of Uzbekistan Islam Karimov said: “Spirituality is the spiritual purification of a person, a unique force that invites the heart to grow, the inner world of man, the will to be strong, the faith to be whole, the conscience to be awakened, it is the criterion of all his views. ” Mother tongue lessons are important in the formation of this spirituality, spiritual and moral qualities.